A Review: Big Data Analytics in Smart Grid Management - Bhawna Dhupia, Sumaya Sanober (International Journal of Advanced Science and Technology, 2020)
Big data is one of the fields which is affecting almost all the scientific field. Be it medical, robotics, smart grid, smart cities big data is playing a vital role in the analysis of data and decision making. It has the potential to unlock the numerous opportunities to enhance all the fields. To date, substantial work has been carried by the researcher in the field of Smart Grid data analytics. They have already discovered the usage of big data analytics in the analysis of smart grid data in the area of planning and operations of the smart grid with a proven record. The widespread use of Advanced Metering Infrastructure (AMI) generates a huge amount of data and it is expected to increase shortly. Due to the complex nature of smart grid data, real-time data transformation, and huge data, the implementation of big data analytics has become challenging. To understand the smart grid analytics process and future challenges, a review is conducted in this paper. This paper discusses the architecture of the smart grid for data collection, stages of data processing and a review of analytical activities in a smart grid for four categories namely, event analytics, state analytics, operational analytics, and customer analytics. In addition to this, the paper also discusses the open research issues of big data analytics in the smart grid.